2009
DOI: 10.21775/cimb.011.047
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardiieffects on gastrointestinal diseases

Abstract: Health benefits attributed to probiotics have been described for decades. They include the treatment and the prevention of gastrointestinal diseases, vaginal and urinary infections and allergies. Saccharomyces boulardii, a species of yeast widely distributed, has been described as a biotherapeutic agent since several clinical trials displayed its beneficial effects in the prevention and the treatment of intestinal infections and in the maintenance of inflammatory bowel disease. All these diseases are character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Several mechanisms have been suggested as to the broad healthpromoting effects of consuming yeast probiotics in humans and span from local general trophic effects to action on both innate and/or adaptive immunity (117,119,120). Clinical trials included mitigation of antibiotic-associated diarrhea; Clostridium difficile diarrhea, irritable bowel syndrome and inflammatory bowel diseases (117,121). Folignè et al (117) tested six yeast strains for anti-inflammatory potential and demonstrated that yeastmediated protection seems to take place predominantly at the level of the intestinal mucosa.…”
Section: Utility Of Yeast Probiotics In Modulating Coccidiosis In Bromentioning
confidence: 99%
“…Several mechanisms have been suggested as to the broad healthpromoting effects of consuming yeast probiotics in humans and span from local general trophic effects to action on both innate and/or adaptive immunity (117,119,120). Clinical trials included mitigation of antibiotic-associated diarrhea; Clostridium difficile diarrhea, irritable bowel syndrome and inflammatory bowel diseases (117,121). Folignè et al (117) tested six yeast strains for anti-inflammatory potential and demonstrated that yeastmediated protection seems to take place predominantly at the level of the intestinal mucosa.…”
Section: Utility Of Yeast Probiotics In Modulating Coccidiosis In Bromentioning
confidence: 99%
“…Although yeasts have been used traditionally for producing different foods and are present as commensals in the gastrointestinal tract, only Saccharomyces boulardii has been shown to have immune modulating properties. S. boulardii is a non-pathogenic yeast used for many years to prevent or treat a variety of human gastrointestinal disorders (Buts, 2008;Buts and De Keyser, 2006;Szajewska et al, 2007;Zanello et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many fungi are commensal and some have been shown to confer health benefits 58,62,155,175 . For example, administration of the probiotic strain S. boulardii has been shown to be effective in ameliorating gastrointestinal diseases 176,177 . In contrast to health benefits, the mycobiota can, however, also act as a reservoir for opportunistic…”
Section: Intestinal Mycobiota Development In Preterm Infantsmentioning
confidence: 99%
“…While many intestinal fungi are commensal and may confer health benefits, fungal overgrowth may lead to infections that are associated with considerable morbidity and mortality rates 155,176,177 . Preterm infants are particularly prone to invasive, systemic candidiasis that affects approximately 10% of preterm infants and has an associated mortality rate of 20% 178,383 .…”
Section: Introductionmentioning
confidence: 99%